2020
DOI: 10.1200/jco.19.03117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgical Excision on the Survival of Patients With Stage 4 High-Risk Neuroblastoma: A Report From the HR-NBL1/SIOPEN Study

Abstract: PURPOSE To evaluate the impact of surgeon-assessed extent of primary tumor resection on local progression and survival in patients in the International Society of Pediatric Oncology Europe Neuroblastoma Group High-Risk Neuroblastoma 1 trial. PATIENTS AND METHODS Patients recruited between 2002 and 2015 with stage 4 disease > 1 year or stage 4/4S with MYCN amplification < 1 year who had completed indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 40 publications
6
59
0
2
Order By: Relevance
“…However, the response to IC is not sufficient in 1/3 of children with high‐risk NB 34,37 . During induction therapy, surgery is performed to resect primary tumor tissue 38,39 . The consolidation phase can provide improved event‐free survival (EFS), especially in NB patients who have undergone tandem ASCT 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, the response to IC is not sufficient in 1/3 of children with high‐risk NB 34,37 . During induction therapy, surgery is performed to resect primary tumor tissue 38,39 . The consolidation phase can provide improved event‐free survival (EFS), especially in NB patients who have undergone tandem ASCT 6 …”
Section: Introductionmentioning
confidence: 99%
“…Surgery represents a cornerstone within the multimodal treatment of NB. The literature supports the idea that a gross total resection is associated with better survival outcomes [54,55]. However, performing a radical NB excision is particularly demanding due to the strict adhesion of the tumour to major blood vessels and nerves and the extensive tumour fibrosis resulting from the neoadjuvant chemotherapy.…”
Section: Targeted Probes For Surgerymentioning
confidence: 77%
“…Direct invasion of the renal parenchyma is detected in 11 to 14% of patients and the renal vasculature is encased or narrowed in 32 to 45% of patients. Kidney-sparing surgery is widely preferred in NB surgical resection, as long as gross total resection is feasible [59]. In a recent study by Fahy et al [60] no significant differences were observed in the survival of patients undergone kidney-sparing surgery, but a better mid-term renal function was revealed in these patients compared to the patients underwent complete nephrectomy.…”
Section: Abdominal Tumorsmentioning
confidence: 99%